EFFICACY AND SAFETY OF SINUS RHYTHM RESTORATION WITH AMIODARONE AND PROPAFENONE IN OUTPATIENTS, ECONOMIC ASPECTS (BASED ON DATA OF N.A. SEMASHKO NORTHERN MEDICAL CLINICAL CENTER) - T. A. Istomina; E. V. Serdechnaya; L. A. Kulminskaya; B. A. Tatarskiy; E. V. Kazakevich; V. L. Lipskiy; S. I. Martyushov (Столичная издательская компания, 2016)
Aim. To study efficacy and safey of sinus rhythm restoration with amiodarone and propafenone in outpatients with recurrent atrial fibrillation (AF), and to estimate pharmacoeconomic efficiency of such cardioversion in comparison with hospital treatment.Material and methods. Patients (n=199; aged 59.2±1.36) with paroxysmal (73.9%) or persistent (26.1%) AF were included into the multicenter prospective study. Follow-up period was 13.14 months (min 1 month, max 36 months). Patients with arrhythmia relapse <48 h received outpatient cardioversion with amiodarone or propafenone orally. Daily outpatient examination, including ECG and blood pressure monitoring every 30-60 min, was carried out to evaluate efficacy of cardioversion and hemodynamics. Phone contact with patients was available. Patients with unstable hemodynamics received cardioversion in hospital. Patients received propafenone in cumulative dose of 600 mg (150-300 mg every hour), and amiodarone 600-800 mg daily. The cost/effectiveness ratio (CER) was estimated. This ratio shows the cost of one unit of effect.Results. Outpatient cardioversion with amiodarone was started 24 h earlier (p=0.029) and with propafenone - 4.5 h earlier (p=0.002) than that in hospital. The average dose of amiodarone in ambulatory cardioversion was 1.3 times less (713.7±84,62 mg, p=0.345) than that in hospital cardioversion. Outpatient treatment with amiodarone restored sinus rhythm 8.7 h earlier, and with propafenone - 3.5 h earlier than the same treatments in hospital. Efficiency of hospital cardioversion with amiodarone was 70%, with propafenone - 80%, and efficiency of outpatient cardioversion - 96,1% and 98,4%, respectively. Outpatient treatment did not cause any severe side effects. Expenses for outpatient cardioversion made up 143 724.25 rubles, and for hospital cardioversion - 92 870.47 rubles. Average treatment costs for one patient in hospital was 6 times greater than for an outpatient. Outpatient cardioversion had the lowest CER (~1300 rubles%).Conclusion. Outpatient cardioversion with amiodarone or propafenone is not only effective and safe, but also economically feasible.